Bandwidth Enhancement of Small Square Monopole Antenna with Dual Band-Notched Characterestics Using H-Ring Slot and Conductor Backed Plane for UWB Applications - Ojaroudi, Mohammad; Ojaroudi, Nasser; Mirhashemi, Seyed Amin (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This article proposes a novel printed monopole antenna for ultra wideband applications with dual band-notch function. The antenna consists of a square radiating patch and a ground plane with H-ring slot and conductor backed plane, which provides a wide usable fractional bandwidth of more than 125% (2.89-13.43 GHz). In order to generate single band-notched characteristic, we use an H-shaped conductor backed plane on the other side of the substrate. By converting this H-shaped conductor backed plane to H-ring form, a dual band-notched function is achieved and also by inserting an H- ring slot in the ground plane, additional resonances are excited and hence much wider impedance bandwidth can be produced, especially at the higher band. The measured results reveal that the presented dual band-notched monopole antenna offers a wide bandwidth with two notched bands, covering all the 5.2/5.8GHz WLAN, 3.5/5.5 GHz WiMAX and 4-GHz C bands. The designed antenna has a small size of 12×18 mm 2 .